Knowledge Management as a Strategic Pillar in Organisational Adaptation to the Dynamics of Business Environment Change - Sulaeman, Moh. Muklis; Suhartono, Edy; Wibowo, Sandi Nasrudin (ADMAN: Journal of Contemporary Administration and Management, 2023)
The current business environment is characterized by rapid and unpredictable changes. Globalization, information technology, regulatory changes, and other economic factors can have a significant impact on organizations. Therefore, organizations need to be able to adapt quickly and effectively to remain competitive in this dynamic market. The purpose of this research is to provide a deeper understanding of the role of knowledge management in assisting organizations in adapting to changes in the business environment. This study employs a qualitative methodology utilizing literature analysis, indicating an exploration and elucidation of information and content derived from diverse documents and texts to form the foundation for analysis. The study results indicate that in the era of globalization and technological advancement, knowledge management is crucial for organizational adaptation to changes in the business environment. This involves the collection, storage, and distribution of knowledge throughout the organization, playing a central role in identifying business trends and supporting internal collaboration. Knowledge management is also essential in understanding customer needs and industry trends, enabling the development of relevant products. Collaboration with business partners through knowledge exchange can strengthen partnerships. To strategically integrate knowledge management, organizations need to build a culture of learning and knowledge sharing, with policies and investments in information technology as key factors for the success of this strategy.